2020
DOI: 10.1093/ehjci/ehaa946.0507
|View full text |Cite
|
Sign up to set email alerts
|

New onset atrial fibrillation after dual chamber pacemaker implantation: long term predictors

Abstract: Background Preserving atrioventricular synchrony has been accepted as a significant advantage of atrial and dual-chamber (DDD) pacing. However, little is known about the incidence of atrial fibrillation (AF) after DDD implantation and its prognostic predictors in long term. Purpose To determine the incidence of new AF episodes and to identify risk factors and prognostic predictors for new-onset AF and all-cause mortality afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A study by V. Ferreira et al showed that the prevalence of new-onset atrial arrhythmia was 51.6 % in patients with dual chamber pacemaker implantation. 13 Another study by Mario Augusto Cray da Costa documented that the prevalence of AF post-PPI was 25 %. 14 Multivariable logistic regression analysis showed that metabolic syndrome, age, coronary artery disease and systolic BP were good independent predictors of atrial arrhythmias among patients who underwent permanent pacemaker implantation.…”
Section: Discussionmentioning
confidence: 99%
“…A study by V. Ferreira et al showed that the prevalence of new-onset atrial arrhythmia was 51.6 % in patients with dual chamber pacemaker implantation. 13 Another study by Mario Augusto Cray da Costa documented that the prevalence of AF post-PPI was 25 %. 14 Multivariable logistic regression analysis showed that metabolic syndrome, age, coronary artery disease and systolic BP were good independent predictors of atrial arrhythmias among patients who underwent permanent pacemaker implantation.…”
Section: Discussionmentioning
confidence: 99%